Diagnostic and surgical management of primary central nervous system angioleiomyoma: A case report and literature review - Emanuele Rubiu; Emanuele Rubiu; Emanuele La Corte; Emanuele La Corte; Giulio Bonomo; Giulio Bonomo; Francesco Restelli; Francesco Restelli; Jacopo Falco; Jacopo Falco; Elio Mazzapicchi; Elio Mazzapicchi; et al. (Frontiers in Oncology, 2022)
Angioleiomyoma (ALM) is a benign smooth muscle neoplasm that mainly occurs in lower extremities subcutaneous tissue and generally affects middle-aged adults. This tumor histotype may rarely localize intracranially, although only a few cases have been described in the literature. We report a case of intracranial ALM, whose differential diagnosis has been particularly challenging, and firstly provide a comprehensive radiological and intra-operative evaluation of a such rare entity. This represents also the first report of the use of intraoperative confocal microscopy in ALM and the first documented short-term recurrence. At this regard, a scoping literature review has been conducted with the aim of presenting the major clinical and diagnostic features along with the proposed therapeutic strategies.